Phonemes Acquisition of An Infant 2 Years Old - Sri Minda; Kartika Rahmadani Rambe (English Education : English Journal for Teaching and Learning, 2021)
This research aimed to investigate the development of language acquisition at two years old especially phonemes acquisition. The data was collected by recording the child’s utterances in daily communication. The record was natural because the utterances recorded while the child was playing by phone. The child uttered without any setting. Based on the data analysis it was found that a child at two years old already able to produce words. Some consonant phonemes which was already produced the child are/b/,/d/, /g/,/k/, /l/, /m/, /n/, /p/, /t/, /y/, /c/. There are 9 variation of consonant phonemes such as /t∫/, /dj/, /ŋ/, /bh/, /dh/, /gh/, /’/, /ch/, /ph/. The total of phonemes acquired by the child is 20 phonemes. Furthermore, the child already can produce vowel phonemes such as /a/, /i/, /u/, /e/, /o/ and 4 variation of vowel phonemes like /∂/, /ʌ/, / ε/, / ô/.